Mixed reality-exploring the requirements of realism in the context of mass casualty incident training - Schulz, Fredrik; Nguyen, Quynh; Baetzner, Anke; Schrom-Feiertag, Helmut; Gyllencreutz, Lina (Prehospital and disaster medicine, 2023)
Introduction:The occurrence of mass casualty incidents is increasing globally. Training is an essential cornerstone in achieving disaster preparedness, yet studies show that medical first responders perceive their level of readiness to face disaster incidents as inadequate. As real-world disaster training exercises can be characterized as resource-intensive in terms of cost and time, virtual training environments have been highlighted as a potential alternative to mass casualty incident training. In order to increase the preparedness of medical first responders, a deeper understanding of their requirements in the context of disaster training exercises is needed.Method:Individual, contextual interviews were conducted with a total of 26 medical first responders from four European emergency service organizations: Hellenic Rescue Team (Greece), Summa 112 (Spain), Sanitätspolizei Bern (Switzerland), and Johanniter Österreich (Austria). The interviews were analyzed using qualitative content analysis.Results:The preliminary results indicate that real-world disaster training exercises have limitations regarding realism. The participants described a need to train in an environment that accurately represents what they might face amidst a real-world incident site. This included the recreation of potential environmental dangers that had to be taken into consideration before approaching the incident site. The participants also highlighted the importance of realistic representations of injuries and reactions from the victims during training. The limited possibilities to provide a realistic training environment that corresponds to the set requirements lead to the participants feeling less prepared to face a real-world mass casualty incident.Conclusion:Medical first responders’ need for increased realism in real-world disaster training exercises deserves attention. Training solutions that could potentially increase the level of preparedness needs to be taken into consideration. How the degree of realism in Virtual or Mixed Reality based training platforms affects the perception of preparedness among medical first responders warrant further research.
Gesehen am 14.08.2023